Business cycle synchronisation in a currency union: Taking stock of the evidence - Nauro F. Campos; Fidrmuc Jarko; Korhonen Iikka (Bank of Finland, 2017)
This paper offers a first systematic evaluation of the evidence on the effects of currency unions on the synchronisation of economic activity. Focusing on Europe, we construct a database of about 3,000 business cycle synchronisation coefficients as well as their design and estimation characteristics. We find that: (1) synchronisation increased from about 0.4 before the introduction of the euro in 1999 to 0.6 afterwards; (2) this increase occurred in both euro and non-euro countries (larger in former); (3) there is evidence of country-specific publication bias; (4) our difference-in-differences estimates suggest the euro accounted for approximately half of the observed increase in synchronisation.
URN:NBN:fi:bof-201709201608
Keywords: E32; F42; 330